2003
DOI: 10.1021/ol034365a
|View full text |Cite
|
Sign up to set email alerts
|

W(CO)5(L)-Catalyzed Endo-Selective Cyclization of Allenyl Silyl Enol Ethers:  An Efficient Method for the Cyclopentene Annulation onto α,β-Unsaturated Ketones

Abstract: [reaction: see text] Indium-mediated allenylation of alpha,beta-unsaturated ketones in the presence of tert-butyldimethylsilyl triflate and dimethyl sulfide gives 6-siloxy-1,2,5-trienes, which undergo W(CO)(5)(L)-catalyzed 5-endo cyclization to give the corresponding cyclopentene derivatives in good yield. Furthermore, this novel W(CO)(5)(L)-catalyzed cyclization of allenyl silyl enol ethers proceeds in a 6-endo manner when 5-siloxy-1,2,5-trienes are employed as a substrate. In these reactions, effective elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In addition, the use of TMSCl as reaction additive also effected the transformation with moderate to good performance . Interestingly, the resulting silyl enol ether products bearing a propargyl or allenyl substituent were able to undergo a W(CO) 5 (THF)- or W(CO) 5 -catalyzed intramolecular cyclization to give the corresponding cyclopentene derivatives in good yields. , …”
Section: Propargylindium and Allenylindium Reagentmentioning
confidence: 99%
“…In addition, the use of TMSCl as reaction additive also effected the transformation with moderate to good performance . Interestingly, the resulting silyl enol ether products bearing a propargyl or allenyl substituent were able to undergo a W(CO) 5 (THF)- or W(CO) 5 -catalyzed intramolecular cyclization to give the corresponding cyclopentene derivatives in good yields. , …”
Section: Propargylindium and Allenylindium Reagentmentioning
confidence: 99%
“…Lee and Iwasawa et al reported that under the catalysis of W(CO) 6 (10 mol %) the allene moiety in 696 can undergo intramolecular endo -mode cyclization with the enol silyl ether moiety. Activation of the terminal CC bond in the allene moiety by the coordination with W(CO) 5 THF may direct the attack of the carbon nucleophile to form 699 , which upon protonolysis would afford 693 (Scheme ) 144 …”
Section: Nucleometalation Reactionsmentioning
confidence: 99%
“…Other acyclic a,b-enones containing n-pentyl (entry 3), phenyl (entries 4 and 6), and 2-thienyl group (entry 5) underwent the Hosomi-Sakurai reaction with almost the same efficiency to afford the desired compounds in good yields. The conjugate addition of allyltrimethylsilane proceeded well in the case of cyclic a,b-enones (entries [7][8][9][10][11][12][13][14]. The reaction of 2-methylcyclopenten-1-one (8a) with allyltrimethylsilane gave 3-allyl-2-methylcyclopentanone (8b) (cis:trans, 1:1.3) in 81% yield (entry 8).…”
Section: Methodsmentioning
confidence: 99%
“…1 Recently, indium(III) chloride-mediated Hosomi-Sakurai reactions were reported. 3 Also, allylbarium, 4 allylcopper, 5 allylindium, 6 and allenylindium 7 have been developed to avoid strongly acidic conditions. The allylation of acyclic a,benones is far more difficult than that of cyclic a,b-enones with these reagents.…”
mentioning
confidence: 99%